Determining factors and variables of trust in the chief-employee relationship in peruvian executives - Aurich-Cornejo, Jorge (2024)
This paper addresses the identification of the most influential factors and variables in the process of building trust in the chief-employees relationship in the context of peruvian executives, distinguishing two groups of factors; personal and behavioral. The research was exploratory and used an original instrument designed to evaluate deeply the issue of trust. As a method of statistical analysis, decision trees were used, a useful machine learning tool in the treatment of non-parametric data. The results obtained show that the behavioral factors are the most important for building trust in the chief-employee relationship; specifically, integrity, communication, consistency, and delegation; factors that, unlike personal factors, are more flexible and let more control for chiefs, and that allow us to conclude and recommend to pay attention and development by managers in their organizations for the enormous relevance of trust as the basis of leadership and people management.